Strategi Diversifikasi Produk Turunan Tenun Sutera Wajo - Karta Jayadi; Abdul Azis Said; Dian Cahyadi (Seminar Nasional LP2M UNM, 2019)
Indonesia has a wealth of various types of beautiful and unique traditional fabrics, one of which is the Sengkang sutera woven fabric. As the dynamics of the times and fashion tastes change, it is necessary to develop a diversified product diversification in accordance with the demands of the times. This research aims to review the strategy model of new product diversification by enriching Sengkang silk woven fabric not only into fabric products for sarong and clothing applications. The method used is data collection, assessment modeling and system development, and evaluation of finished products. This activity produced a development strategy direction as an effort to diversify Sengkang silk weaving products to have a stronger product competitiveness and image